ChemInform Abstract: Nickel‐Catalyzed Carbon—Carbon Bond‐Forming Reactions of Unactivated Tertiary Alkyl Halides: Suzuki Arylations. Issue 26 (6th June 2013) - Zultanski, Susan L.; Fu, Gregory C.
Abstract The first examples for both the Suzuki‐type cross‐coupling of unactivated tertiary alkyl electrophiles and the application of a group 10 catalyst to cross‐couple this type of electrophiles are presented.